Analisis Penerapan Metode Bercerita dalam Menghadapi Siswa dengan Keterlambatan Bicara (Speech Delay) pada Program Kelas Inklusif di MI Cibangbay Kab. Tasikmalaya - Nur Islamy, Astri; Syifa Fauziah Azmi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2024)
The aim of this research is to describe: the application of the storytelling method as an effort to handle students with speech delays in the inclusive education program at MI Cibangbay Kab. Tasikmalaya. The method used in this research is descriptive qualitative with a qualitative approach, where data collection techniques are obtained through observation, interviews and document review. Based on this research, the following results were obtained: (1) The ability of students with speech delays before using the storytelling method was seen from very passive (difficult to understand) conversations where students were not yet able to communicate, either with their teacher or with their friends. Meanwhile, when viewed from a social perspective, students tend to be quiet and reluctant to socialize with their friends. (2) The storytelling method is very effective in dealing with children with speech delays. Storytelling can be a fun learning method. The application of the storytelling method at MI Cibangbay is through the teacher's steps in communicating the theme of the story, arranging seating, opening activities, story content and closing. So, when using the storytelling method, there needs to be criteria for selecting a good story for students, including: the story must be interesting, adapted to the child's age, and choosing a theme must be adapted to the material being presented. (3) The ability of students with speech delays after using the storytelling method experienced good development, namely that students gradually began to be able to pronounce words even though they still stammered with quite loud intonation. Also, students begin to show an open attitude (socialize) with their friends and do not cry easily.